2016
DOI: 10.1051/0004-6361/201629512
|View full text |Cite
|
Sign up to set email alerts
|

GaiaData Release 1

Abstract: Context. At about 1000 days after the launch of Gaia we present the first Gaia data release, Gaia DR1, consisting of astrometry and photometry for over 1 billion sources brighter than magnitude 20.7. Aims. A summary of Gaia DR1 is presented along with illustrations of the scientific quality of the data, followed by a discussion of the limitations due to the preliminary nature of this release. Methods. The raw data collected by Gaia during the first 14 months of the mission have been processed by the Gaia Data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
272
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 1,740 publications
(281 citation statements)
references
References 33 publications
6
272
0
1
Order By: Relevance
“…The star itself is a Herbig Fe star of spectral type F6 IIIe (M≈1.8 M ) at a distance of 156 +7 −6 pc (Gaia Collaboration et al 2016) in the Sco-Cen association (Biller et al 2012;Mendigutía et al 2014). Modelling of the Spectral Energy Distribution (SED) suggested a disc gap between 30 and 130 au (Verhoeff et al 2011), confirmed by the initial ALMA observations .…”
Section: Danielprice@monashedumentioning
confidence: 56%
“…The star itself is a Herbig Fe star of spectral type F6 IIIe (M≈1.8 M ) at a distance of 156 +7 −6 pc (Gaia Collaboration et al 2016) in the Sco-Cen association (Biller et al 2012;Mendigutía et al 2014). Modelling of the Spectral Energy Distribution (SED) suggested a disc gap between 30 and 130 au (Verhoeff et al 2011), confirmed by the initial ALMA observations .…”
Section: Danielprice@monashedumentioning
confidence: 56%
“…Such a model is called an errors-in-variables model (also known as the measurement error model) and has been studied extensively in the statistics literature, see e.g. Fuller (1987). Here, we have the additional feature that the variances of both η i and ε i have been quantified.…”
Section: Nearby Kepler Dwarfs and Subgiantsmentioning
confidence: 99%
“…Furthermore, the Hubble Space Telescope Fine Guidance Sensor cameras were used by Benedict et al (2011) to determine trigonometric parallaxes to several of the nearest field RR Lyr, in principle providing a fundamental calibration for all these efforts. Sesar et al (2017a) used the Tycho-Gaia Astrometric Solution (Michalik et al 2015) parallaxes of nearby RR Lyr from the Gaia Data Release 1 (Brown et al 2016) to verify existing period-luminosity-metallicity relationships of previous studies, illustrating the potential for very high accuracy distances for RR Lyr stars with future Gaia releases.…”
Section: Introductionmentioning
confidence: 97%
“…S. G. Djorgovski) and the Pan-STARRS survey (Hodapp et al 2004;Tonry et al 2012), with the Large Synoptic Survey Telescope (LSST) coming in the next decade. Gaia recently had its first data release as well (Brown et al 2016), with more to follow in due course. These surveys, with their huge databases, can, depending on their cadences and limiting magnitudes, be used to identify ever-larger samples of ever more distant RR Lyr, continuing and expanding on much earlier efforts (see, e.g., Wetterer & McGraw 1996).…”
Section: Introductionmentioning
confidence: 99%